The Effectiveness of the Use of the SIAPIK Application at PT Liefde Herb Nusantara with the PIECES Approach - Cinta Liantri; Rika Nalinda; Fitria Naimatu Sadiyah (JABKO: Jurnal Akuntansi dan Bisnis Kontemporer, 2026)
Unstructured manual financial recording is often an obstacle to the growth of MSMEs in the herbal sector, including PT Liefde Herb Nusantara. To overcome these problems, the company implemented the SIAPIK (Financial Information Recording Application Information System) application from Bank Indonesia. This study aims to analyze the effectiveness of the use of the SIAPIK application at PT Liefde Herb Nusantara using the PIECES (Performance, Information, Economy, Control, Efficiency, and Service) approach. The method used is quantitative descriptive. Data is collected through interviews, observations, and transaction documentation. The results showed that the implementation of SIAPIK increased the effectiveness of financial management across all dimensions of PIECES, with the overall average score increasing from 2.85 under the manual system to 4.35 after the implementation of the SIAPIK application. This research proves that digitizing financial records through SIAPIK can be a strategic solution for herbal MSMEs in producing accurate financial reports according to SAK EMKM standards.